Mechanistic Studies on the Palladium‐Catalyzed Direct C‐5 Arylation of Imidazoles: The Fundamental Role of the Azole as a Ligand for Palladium. Issue 4 (26th January 2016) - Perego, Luca Alessandro; Grimaud, Laurence; Bellina, Fabio
Abstract: An in‐depth mechanistic study on the palladium‐catalyzed direct arylation of imidazoles at the C‐5 position is presented. The interactions of triphenylphosphine (PPh3 )‐ligated aryl‐Pd species with 1, 2‐dimethyl‐1 H ‐imidazole (dmim) have been studied in detail. In contrast with previous suggestions, phosphine‐ligated organo‐Pd species are not active and the reaction proceeds through imidazole‐ligated organo‐Pd intermediates. The kinetics of the oxidative addition of aryl halides with dmim‐ligated Pd(0) species have been characterized in a Pd(dba)2 /dmim model system. A thorough study of the equilibria involving novel [ArPd(dmim)2 X] complexes (X=I, OAc) and the unexpected cationic [ArPd(dmim)3 ] + is also reported. The ability of these species to effect the CH arylation of dmim at room temperature in the presence of acetate is also demonstrated. Abstract :